2012
DOI: 10.1186/1475-2875-11-217
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and tolerability of artemisinin-piperaquine (Artequick®) versus artesunate-amodiaquine (Coarsucam™) for the treatment of uncomplicated Plasmodium falciparum malaria in south-central Vietnam

Abstract: BackgroundIn Vietnam, the artemisinin-based combination therapy (ACT) of dihydroartemisinin-piperaquine is currently used for first-line treatment of uncomplicated Plasmodium falciparum malaria. However, limited efficacy and tolerability data are available on alternative forms of ACT in Vietnam in case there is a reduction in the susceptibility of dihydroartemisinin-piperaquine. A study was conducted to compare the efficacy and tolerability of two fixed-dose formulations of ACT, artemisinin–piperaquine (Artequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 36 publications
3
39
0
Order By: Relevance
“…For these reasons, amodiaquine may show some useful efficacy in SEA. This is also consistent with the acceptable clinical efficacy of artesunate–amodiaquine in some [59, 60], but not all [61], parts of SEA within the last decade. Furthermore, the inverse correlation between susceptibility to 4-aminoquinolines and mefloquine [62, 63] offers the potential to combine two partners with opposing resistance mechanisms within a novel ‘triple’ ACT, artemether–lumefantrine plus amodiaquine [64]; this is currently under investigation in the follow-up study to TRAC (ClinicalTrials.gov NCT02453308).…”
Section: Discussionsupporting
confidence: 83%
“…For these reasons, amodiaquine may show some useful efficacy in SEA. This is also consistent with the acceptable clinical efficacy of artesunate–amodiaquine in some [59, 60], but not all [61], parts of SEA within the last decade. Furthermore, the inverse correlation between susceptibility to 4-aminoquinolines and mefloquine [62, 63] offers the potential to combine two partners with opposing resistance mechanisms within a novel ‘triple’ ACT, artemether–lumefantrine plus amodiaquine [64]; this is currently under investigation in the follow-up study to TRAC (ClinicalTrials.gov NCT02453308).…”
Section: Discussionsupporting
confidence: 83%
“…A total of 11 different clinical studies were shared with WWARN, containing 8,776 plasma piperaquine concentrations from 728 individuals that could be included in the pooled analysis (Fig 1) [22,24,25,27,29,30,3943]. Demographic data are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Study reports generated from the formatted datasets were sent back to investigators for clarification and/or validation. Pharmacokinetic data from ten previously published clinical studies and one unpublished (at the time) clinical study were contributed and used for modelling [22,24,25,27,29,30,3943]. Demographic data from each study are summarised in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have reported good efficacy of DHAPQ combination for malaria treatment [23-25]. The three antimalarial drugs remained highly effective at days 35 and 42.…”
Section: Discussionmentioning
confidence: 99%